Study various clinical manifestations and biochemical parameter for liver dysfunction in association with Plasmodium vivax malaria - Banthia, Bajranglal; Shakir, Saad Mohammad (International Journal of Research in Medical Sciences, 2020)
Background: Malaria is a parasitic disease which is majorly caused by the bite of an infected Anopheles mosquito. It has been estimated that the most common type of malaria affecting the human race is known as Plasmodium vivax. Human malaria is a global burden with 3.4 billion people at risk over 91 endemic countries. According to the WHO, the involvement of liver dysfunction in Plasmodium vivax malaria is not an uncommon phenomenon. Aim of the research was to study various clinical manifestations and biochemical parameter for liver dysfunction in association with Plasmodium vivax malaria. Methods: It was an observational study carried out at Teerthanker Mahaveer Medical College and Research Centre, a tertiary care hospital situated in Moradabad for a period of 1 year (March 2017-Feb 2018). Total of 200 patients aged above 15 years, with either sex were part of it. All the patients having mixed malaria with dengue, pregnant women and the patients who did not give written consent for being a part of the study were excluded from the study. A detailed clinical examination was done, including all the hematological and biochemical examinations. Results: The results depicted that the number of male patients was 95, and the number of female patients was 105. The majority of the patients belonged to 15-30 years of age group. The major clinical features of the patients suffering from P. Vivax were fever and jaundice. The number of patients with serum bilirubin >3 mg/dl was 55. Conclusions: In light of the above results, it was evident that Plasmodium vivax has the capability of producing jaundice, hepatic dysfunction and anemia. The doctors must be very vigilant while treating the patients with Plasmodium vivax for any symptoms of jaundice as they are often misunderstood as hepatitis.